Evaluation of dried skim milk, dried whey, and fat in pig starters - J G Stuart; B A Koch; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1970)
Five starters were compared with a corn-soybean meal standard with 15% skim milk and 12% sugar. Rations containing dried skim milk or dried whey with 3 or 5% added edible fat also were compared. The rations were offered to suckling baby pigs from 2 to 4 weeks (phase 1) and again during 6 to 10 weeks of age (phase 2). During phase 1, neither feed intake nor total gain differed significantly. During phase 2 all rations produced similar weight gains and feed intake. Feed efficiency favored rations containing dried skim milk and 3 or 5% added fat. Rations containing more fat produced more efficient gains.; Swine Day, Manhattan, KS, October 1, 1970
Keywords: Swine day; 1970; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 163; Swine; Dried skim milk; Dried whey; Fat